Resistive index as a predictor of renal progression in patients with moderate renal dysfunction regardless of angiotensin converting enzyme inhibitor or angiotensin receptor antagonist medication - Jae Hoon Kim; Su Mi Lee; Young Ki Son; Seong Eun Kim; Won Suk An (The Korean Society of Nephrology, 2017)
Background: Previous studies have shown that a higher resistive index (RI) on renal duplex ultrasonography was related with renal progression and acute kidney injury, especially in patients with chronic kidney disease (CKD) using an angiotensin converting enzyme inhibitor (ACEI) or angiotensin receptor antagonist (ARB). We evaluated whether a RI value is a predictive factor for renal progression regardless of ACEI or ARB medication in patients with moderate renal dysfunction. Methods: We retrospectively analyzed 119 patients with moderate renal dysfunction that had been evaluated with renal duplex ultrasonography from February 2011 to April 2015. Moderate renal dysfunction was defined as a stage 3 to 4 CKD. Renal progression was defined as a doubling of the baseline serum creatinine (sCr), a decrease of baseline glomerular filtration rate by > 50%, or initiation of renal replacement therapy. Results: The mean age was 64.7 ± 11.0 years and sCr level was 2.1 ± 1.2 mg/dL. The RI ≥ 0.79 group showed a higher incidence of renal progression (P = 0.004, log-rank test) compared with the RI < 0.79 group, irrespective of ACEI or ARB usage. In the Cox proportional hazard model, RI ≥ 0.79 was an independent prognostic factor after adjusting for age, sex, diabetes mellitus, sCr, proteinuria, and use of ACEI or ARB (hazard ratio, 4.88; 95% confidence interval, 1.06-22.53; P = 0.043). Conclusion: RI ≥ 0.79 on the renal duplex ultrasonography can be a helpful predictor for renal progression in patients with moderate renal dysfunction, regardless of their ACEI or ARB usage.